Self-directed learning in e-portfolios: Analysing students' performance and learning presence - A. Jimoyiannis; P. Tsiotakis (European Alliance for Innovation (EAI), 2016)
E-portfolios constitute a dynamic research topic in e-learning, since they foster a new philosophy for learning and personal development, which is characterised by open, participatory, self-directed, reflective and collaborative processes. This paper presents an investigation on students' learning presence in a blended post-graduate course, designed to promote self directed learning through e-portfolio activities. The theoretical foundations and the key dimensions of e-portfolio learning activities are outlined, i.e. students' construction, reflection and collaboration. Following are presented the organizational and the analysis framework of students' self-directed learning and constructive activities within the e-portfolio. Combining both, descriptive analysis and Social Network Analysis of the research data, we have revealed important information regarding individual performance and students' learning presence, interaction and collaboration among participants as well as the overall operation of the e-portfolio community.